2017
DOI: 10.2147/cia.s113240
|View full text |Cite
|
Sign up to set email alerts
|

Bone cement distribution in the vertebral body affects chances of recompression after percutaneous vertebroplasty treatment in elderly patients with osteoporotic vertebral compression fractures

Abstract: ObjectivePercutaneous vertebroplasty (PVP) is a surgical procedure that has been widely used to treat patients suffering from osteoporotic vertebral compression fractures (OVCFs). The procedure involves injection of bone cement into a fractured vertebra. In this study, we investigated whether the distribution of the cement in the vertebral body is related to the occurrence of recompression after surgery.Patients and methodsA total of 172 patients diagnosed with OVCF, from January 2008 to June 2013, were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 13 publications
5
64
1
Order By: Relevance
“…Ahn et al 21 found that differences in vertebral body strength caused by bone cement augmentation resulted in fractures of adjacent vertebral bodies, while the difference in segmental mobility caused fractures of non-adjacent vertebral bodies. Recently, Zhang et al 22 showed that vertebral body augmentation does not increase untreated vertebral fractures. Compared with the patients in the OOVF group, the preoperative bone mineral density of patients in the N-OOVF group was worse, and the postoperative adjacent vertebral fracture rate in the OOVF group was lower than in the N-OOVF group.…”
Section: Discussionmentioning
confidence: 99%
“…Ahn et al 21 found that differences in vertebral body strength caused by bone cement augmentation resulted in fractures of adjacent vertebral bodies, while the difference in segmental mobility caused fractures of non-adjacent vertebral bodies. Recently, Zhang et al 22 showed that vertebral body augmentation does not increase untreated vertebral fractures. Compared with the patients in the OOVF group, the preoperative bone mineral density of patients in the N-OOVF group was worse, and the postoperative adjacent vertebral fracture rate in the OOVF group was lower than in the N-OOVF group.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that patients with bone cement distributed around both the upper and lower endplates had the lowest rate of experiencing recompression compared to other patterns of bone cement distribution. 24 Previous studies showed that a larger bone–cement interface would achieve a relatively higher vertebral strength and reduce leakage rate. 25 It was suggested that the cement should spread through the vertebral body in a controlled manner that appeared fluoroscopically as a “uniformly expanding cloud” 26 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies examining if the location, amount, and type of cement injected affected the outcome of vertebral augmentation. The distribution of cement is important since failure to obtain an adequate spread of the cement into the fractured area and specifically near the fractured endplates may lead to further collapse [ 19 ]. Even hemivertebral filling does not affect the risk of recurrent fractures at adjacent levels [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…This highlights that the surgeon needs to make sure the injected cement gets to the area of the fracture, the involved endplate, and the edematous part of the vertebra. Studies have shown that low volumes (up to three cc of cement) are sufficient to stabilize the compression if well distributed, especially along the fractured endplates [ 8 , 17 , 19 - 20 ]. In repeat cases, both the superior and inferior endplates should be treated to provide complete support to progressively collapsing vertebrae (Figure 4 ).…”
Section: Reviewmentioning
confidence: 99%